(untitled) (Cadernos de Sociomuseologia, 2010)
Half a century, from 1947 to 2010, is enough for us to take stock of the impact of the “ideology of Development” on Heritage. An ideology induced by UNESCO and by ICOM. What has changed and what is still in an impasse? What effects has this ideology had on Heritage? It is after making this assessment that we can better understand the extent to which the theme of this 22nd ICOM General Conference – Shangai 2010 is ultimately an obvious product of that influence.